2012
DOI: 10.1007/s10620-012-2055-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and the Incidence of Colorectal Cancer: An Updated Systematic Review and Meta-Analysis

Abstract: Our findings further support a relationship between diabetes and increased risk of colon and rectal cancer in both women and men, and insulin therapy for diabetes may increase this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
109
3
7

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(132 citation statements)
references
References 42 publications
13
109
3
7
Order By: Relevance
“…Twelve of these articles also included meta-analysis of observational studies [4, 5, 10, 12, 18-21, 27, 49, 55, 62]. Another 14 articles on meta-analyses of observational studies were also identified [63][64][65][66][67][68][69][70][71][72][73][74][75][76] ( Table 1). The meta-analyses addressed diverse medications including antidiabetics, antihyperlipidemics, antihypertensives, antirheumatics, drugs for osteoporosis, and drugs for other conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve of these articles also included meta-analysis of observational studies [4, 5, 10, 12, 18-21, 27, 49, 55, 62]. Another 14 articles on meta-analyses of observational studies were also identified [63][64][65][66][67][68][69][70][71][72][73][74][75][76] ( Table 1). The meta-analyses addressed diverse medications including antidiabetics, antihyperlipidemics, antihypertensives, antirheumatics, drugs for osteoporosis, and drugs for other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…At least one other meta-analysis [72] shows no risks or decreased risks with these antihypertensive agents. Insulin therapy seemingly has the strongest evidence for an association with increased overall cancer risk, and this is also reflected in significant associations with specific cancer types, in particular colorectal and pancreatic cancers which have each been documented in two separate meta-analyses [63][64][65]. However, a recent large randomized, trial on over 12 000 randomized participants (ORIGIN) found no increased risk of cancer with insulin versus standard care over a median follow-up of 6.2 years [83].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, IGFBP1 methylation levels in peripheral blood were recently found increased in type II diabetic men compared with normal glucose-tolerant individuals (12). Type II diabetics as compared with nondiabetics have been found to be at an increased risk of colorectal cancer (13).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a common chronic disease associated with increased incidence of cancer at various sites (including colon and rectum) compared with general or nondiabetic populations [1][2][3][4]. Pre-existing diabetes at cancer diagnosis is also associated with poorer overall survival in patients with colorectal cancer (CRC) [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%